MENJAGA MUTU LAYANAN MELALUI PRAKTIK KERJA YANG BERTANGGUNG JAWAB: REFLEKSI KUALITATIF ATAS DINAMIKA ETIKA, DISIPLIN, DAN KOMITMEN PEGAWAI - Mawar Nauli; Miska Irani Br Tarigan; Donalson Silalahi; Harum Nauli; Julivacius Gok Asi Sinambela (Berajah Journal, 2025)
Service quality reflects the quality of human resources who carry out their duties and responsibilities professionally. This study aims to explore the dynamics of employee ethics, discipline, and commitment in shaping responsible work practices and their contribution to organizational service quality. Using a descriptive qualitative approach, this study reveals that these three aspects are interrelated and play a strategic role in creating consistent, integrated, and user-satisfaction-oriented services. Work ethics serve as the moral foundation for decision-making; discipline reinforces order in task execution; while commitment fosters loyalty and dedication to the organization. However, employees also face a number of challenges, such as structural pressures, a permissive organizational culture, and high workloads. To overcome these obstacles, employees develop various strategies such as strengthening intrinsic motivation, fostering solidarity among colleagues, and fostering ethical communication. This study recommends the importance of creating a work system that supports the integration of ethical values, discipline, and commitment as a foundation for maintaining sustainable service quality.